Community Education Variables and Rural Development Activities of Community-Based Organisations in Rural Areas of Ogun State, Nigeria. - Adeniyi, Adekunle A.; Aderogba, Kofo (NIU Journal of Social Sciences, 2019)
This study investigated the variables facilitating community education and their relationship with rural development activities of community-based organisations. Ex post facto design was adopted and 100 participants were selected using simple random sampling technique. Analysis of data generated from the instrument with 0.73 reliability showed effectiveness of community education variables used. PPMC matrix showed there was a positive significant relationship between community education variables and rural development activities of community-based organisations. It is recommended that community education programs designed for rural transformation must focus more on all its variables and not only on literacy. Keywords: Community education; development; community-based organisations; rural areas .